Otimização de altitude de vôo para aeronaves executivas para economia de combustível e tempo - Sousa Junior, Albano Freire [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This work approaches, in a simplified manner, the analysis of an aircraft’s trajectory through the 3 main flight phases, climb, cruise and descent, related to fuel consumption and elapsed time. From this analysis is developed a tool that aims optimize the flight planning operational procedure, providing an altitude that comply with fuel saving during the trip, or minimizes the trip time. The use of any altitude is an operator’s decision, that aims comply with their operational needs of each trip, getting the results provided by the tool as a primary approach to the flight profile that also bring up economics aspects of each possibility of decision to be taken. Since the aeronautical Market has singular problems, as the flight altitude optimization, there is the need to solutions very customized that many times can not attend every restriction for each operator and its related kind of operation. When we talk about executive aircrafts, is possible to note that its operators does not have enough engineering and logistic support, when compared to huge airlines companies, to analyze all exceptions of each singular operation, creating many times wastes that can be avoiding with a tool described herein in this work

Neste trabalho aborda-se, de forma simplificada, a analise da trajetória de uma aeronave percorrendo as 3 principais fases de um vôo, subida, cruzeiro e descida, com relação ao consumo de combustível e tempo. A partir desta analise é desenvolvida uma ferramenta que visa otimizar o procedimento operacional de planejamento de vôo, fornecendo uma altitude que atende a economia de combustível durante a viagem, ou minimiza o tempo de viagem. A utilização de uma das altitudes fica a critério do operador, que procura atender as necessidades operacionais de cada viagem, ficando os resultados fornecidos pela ferramenta como uma primeira aproximação para o perfil de vôo que também levanta os aspectos econômicos de cada possibilidade de decisão a ser tomada. Como o mercado aeronáutico tem problemas bem específicos, como a otimização da altitude de vôo, existe a necessidade de soluções bem customizadas que muitas vezes podem não atender todas as restrições para cada operador e seu respectivo tipo de operação. Quando tratamos de aeronaves executivas, observamos operadores que não tem um suporte de engenharia e logísticos suficientes, quando comparados com grandes companhias aéreas, para analisar todas as exceções de sua operação especifica, criando muitas vezes desperdícios que podem ser evitados com uma ferramenta como a descrita neste trabalho
Keywords: Aviões; Vôo; Altitudes